Early civil law codification efforts in the Principality of Serbia - Nikolić, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
This paper is a synthesis of research results stemming from the author’s earlier studies on the unsuccessful attempt of drafting the first civil code in the Principality of Serbia in the period from 1829 to 1835. The failure of this codification effort is observed in light of several important historical facts reflecting the relations between Prince Miloš Obrenović and the Legislative Committee. Prince Miloš was indeed the one who initiated the drafting of the civil code, which was to be modelled on the French Civil Code of 1804. Moreover, the Committee membership was appointed by the Prince himself. Yet, in the specific historical circumstances, the Prince’s initiative was actually a political move largely forced by the widespread discontent with his autocratic rule without enacting legislation. Many indications suggest that Prince Miloš assumed that the public discontent would subdue if he were recognized in the public eye as the one who had established the Legislative Committee for drafting the civil code, and that it would suffice to allow the Committee to embark on the codification work. Yet, Prince Miloš was not genuinely interested in a successful outcome of this project. It is rather symptomatic that the members of the Legislative Committee, which were appointed by the Prince himself, had no legal knowledge and skills for such a serious codification project. On the other hand, Prince Miloš frequently acted on his own accord, kept changing the Committee members without any explanation, allowed frequent interruptions and long periods of inactivity, and granted long leaves of absence to individual members of the Committee. When the Committee finally prepared the draft version of the civil code, Prince Miloš was highly negative and critical about it, and he practically dismissed it altogether. The manuscript of this draft civil code has not been preserved in the historical archives. Bits and pieces of its content may barely be reconstructed, mainly by examining the contents of letters in which Prince Miloš passed his extremely negative remarks and extended his criticism on the draft civil code. Key words: codification of civil law, Principality of Serbia, drafting the civil code, Prince Miloš Obrenović